Evasion of Antiviral Innate Immunity by Porcine Reproductive and Respiratory Syndrome Virus - Wang, Tong-Yun; Sun, Ming-Xia; Zhang, Hong-Liang; Wang, Gang; Zhan, Guoqing; Tian, Zhi-Jun; Cai, Xue-Hui; Su, Chenhe; Tang, Yan-Dong (Frontiers in Microbiology, 2021)
Innate immunity is the frontline for antiviral immune responses and bridges adaptive immunity against viral infections. However, many viruses have evolved multiple strategies to evade host innate immune surveillance. A typical virus is the porcine reproductive and respiratory syndrome virus (PRRSV), one of the most globally devastating viruses threatening the swine industry worldwide. PRRSV engages several strategies to evade the porcine innate immune responses. In this review, we focus on the underlying mechanisms employed by PRRSV to evade pattern recognition receptors (PRRs) signaling pathways, type I interferons (IFN-α/β) receptor (IFNAR)-JAK-STAT signaling pathway, and interferon-stimulated genes (ISGs). Deciphering the antiviral immune evasion mechanisms by PRRSV will enhance our understanding of PRRSV's pathogenesis and help us to develop more effective methods to control and eliminate PRRSV.